2006
DOI: 10.1542/peds.2005-2699
|View full text |Cite
|
Sign up to set email alerts
|

Statewide Quality Improvement Outreach Improves Preventive Services for Young Children

Abstract: The work in this project has provided the evidence for an effective statewide pediatric quality improvement outreach program to improve preventive services for children who are younger than 5 years. Practices' decision to focus on a specific preventive service area as a quality improvement goal seems necessary for improvement in that area. This approach may be effective in other states or regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Shaw et al 6 and Young et al 31 showed that practices who set goals and used QI methods achieved improvement in at least 1 preventive service. In accordance with recommendations by Solberg et al, 32 we used strategies that considered multiple characteristics of participating clinics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shaw et al 6 and Young et al 31 showed that practices who set goals and used QI methods achieved improvement in at least 1 preventive service. In accordance with recommendations by Solberg et al, 32 we used strategies that considered multiple characteristics of participating clinics.…”
Section: Discussionmentioning
confidence: 99%
“…2 Past efforts to improve quality in pediatric primary care have focused mostly on individual services, such as improving immunization rates 3 or lead screening. [4][5][6] Yet, pediatric practices continue to struggle with comprehensively delivering preventive services in light of lengthy abstract BACKGROUND AND OBJECTIVES: Previous studies have documented poor rates of delivery of preventive services, 1 of the core services provided in the primary care medical home setting. We aimed to increase the reliability of delivering a bundle of preventive services to patients 0 to 14 months of age from 58% of patient visits to 95% of visits.…”
mentioning
confidence: 99%
“…The project measured a combination of nationally endorsed measures and measures tested in and/or adapted from previous QI preventive services projects. 8,11,12,[15][16][17][18][19] Measurements included in the PreSIP are detailed in Table 2. One particularly challenging but critical measurement area was the "partnership with parents," a unique and integral component of Bright Futures not reflected in adult practice guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…She reviewed and revised the manuscript, making several significant additions for tables; Dr Shaw contributed to the conceptualization and design of the study, participated as faculty at the first learning session, and reviewed the manuscript with hospitals, meeting over a defined timeframe to effect the specific change targeted for improving care. [8][9][10][11][12][13] A natural extension of the collaborative model is an organized network of providers or institutions engaging its members in topic-specific collaboratives. In 2005, the American Academy of Pediatrics (AAP) developed the Quality Improvement Innovation Networks (QuIIN) to organize a platform of practices for testing "change packages" of new measures, guidelines of care, and innovative care delivery approaches before widespread dissemination.…”
mentioning
confidence: 99%
“…initiatives 11,12 and regional improvement partnerships involving chapters of the American Academy of Pediatrics~AAP! 13,14 have successfully changed practice using these concepts.…”
Section: Introductionmentioning
confidence: 99%